Analisa Kritis Hegemonic Transition Theory dan Middle Power Diplomacy dalam Kebijakan Luar Negeri Indonesia pada Keanggotaan Board Of Peace - Wibisono, Adhe Nuansa; Sudiarto, Tatok Djoko (Jurnal Ragam Pengabdian, 2026)
This article critically examines the application of Hegemonic Transition Theory and middle power diplomacy to explaining Indonesia's foreign policy of joining the Board of Peace (BoP), a body established by U.S. President Donald Trump in January 2026. Amidst the erosion of the liberal order and the shift toward multipolarity, Indonesia's decision sparked domestic debate. Some viewed it as a strategic pragmatic step, while others viewed it as a violation of the “free and active” principle. Using qualitative descriptive-analytical methods, coupled with literature review and source triangulation, this article finds Hegemonic Transition Theory relevant to explaining the systemic conditions driving Indonesia's move. The theory explains the pressures from unilateral hegemonic actions and the need for middle-power states to remain relevant amidst the uncertainty of global power transitions. Furthermore, the concept of middle power diplomacy enriches the analysis by explaining Indonesia's hedging and multi-alignment strategies. This research emphasizes the need for Indonesia to maintain a multi-alignment approach that makes the BoP one, not the only, diplomatic arena, while continuing to strengthen its networks in BRICS, the Non-Aligned Movement, and other multilateral forums.